Bumi prasangka / Budi Jaya Putra; penyunting, Hatib Rahmawan; editor, Salma Sara Jevo, Fitri Agustin - BUDI JAYA PUTRA, 1981-; HATIB RAHMAWAN; SALMA SARA JEVO; FITRI AGUSTIN (Semesta Ilmu, 2015)
x, 108 hlm. ; 21 cm.